2014
DOI: 10.1371/journal.pone.0088433
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Gene Flow between Two Sympatric Mealybug Species (Insecta; Coccoidea; Pseudococcidae)

Abstract: Occurrence of inter-species hybrids in natural populations might be evidence of gene flow between species. In the present study we found evidence of gene flow between two sympatric, genetically related scale insect species – the citrus mealybug Planococcus citri (Risso) and the vine mealybug Planococcus ficus (Signoret). These species can be distinguished by morphological, behavioral, and molecular traits. We employed the sex pheromones of the two respective species to study their different patterns of male at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
(118 reference statements)
1
17
0
Order By: Relevance
“…High mortality among hybrid male crawlers was also documented in that study (Rotundo and Tremblay 1982). In a previous study, we used pherotype compositions and ITS2 gene sequences to demonstrate the occurrence of gene flow between P. citri and P. ficus among wild populations (Kol-Maimon et al 2014), and the results suggested a directional gene flow from P. ficus to P. citri but not vice versa. We further showed that genetic features of P. ficus were present among P. citri populations but not vice versa.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…High mortality among hybrid male crawlers was also documented in that study (Rotundo and Tremblay 1982). In a previous study, we used pherotype compositions and ITS2 gene sequences to demonstrate the occurrence of gene flow between P. citri and P. ficus among wild populations (Kol-Maimon et al 2014), and the results suggested a directional gene flow from P. ficus to P. citri but not vice versa. We further showed that genetic features of P. ficus were present among P. citri populations but not vice versa.…”
Section: Introductionmentioning
confidence: 51%
“…Chromatograms showing double peaks among representative type H sequences likewise served as an indication for heterozygosity of those sequences ( Fig. 3; Kol-Maimon et al 2014). By means of the BioPerl software, the probability for each nucleotide to occupy each position in the amplified ITS2 segment (see Tables S1 and S2 for the analysis) was calculated, and the expected proportion-8 %-of single-nucleotide polymorphisms (SNPs) that differentiate P. citri from P. ficus was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations